Activated hepatic stellate cells secrete periostin to induce stem cell-like phenotype of residual hepatocellular carcinoma cells after heat treatment - Rui Zhang (Nature Portfolio, 2017)
Abstract Some evidences show that residual tumor after thermal ablation will progress rapidly. However, its mechanisms remain unclear. Here, we assessed whether activated HSCs could regulate stem cell-like property of residual tumor after incomplete thermal ablation to promote tumor progression. Human HCC cell lines were exposed to sublethal heat treatment to simulate the peripheral zone of thermal ablation. After residual HCC cells were cultured with conditional medium (CM) from activated HSCs, parameters of the stem cell-like phenotypes were analyzed. Nude mice bearing heat-exposed residual HCC cells and HSCs were subjected to metformin treatment to thwarter tumor progression. CM from activated primary HSCs or LX-2 cells significantly induced the stem cell-like phenotypes of residual HCC cells after heat treatment. These effects were significantly abrogated by neutralizing periostin (POSTN) in the CM. POSTN regulated the stemness of heat-exposed residual HCC cells via activation of integrin β1/AKT/GSK-3β/β-catenin/TCF4/Nanog signaling pathway. Metformin significantly inhibited in vivo progression of heat-exposed residual HCC via suppressing POSTN secretion and decreasing cancer stem cell marker expression. Our data propose a new mechanism of activated HSCs promoting the stemness traits of residual HCC cells after incomplete thermal ablation and suggest metformin as a potential drug to reverse this process.